FORMATION OF PSYCHOLOGICAL THINKING IN THE STUDY OF LATIN LANGUAGE IN MEDICAL HIGHER EDUCATION INSTITUTIONS (Web of Teachers: Inderscience Research, 2025)
This article discusses the development of psychological thinking of medical students and the methods of using various concepts in teaching Latin.